Leadership in Nursing: Styles, Challenges, and Barriers - Kamaryati, Ni Putu; Putu Darma Suyasa, I Gede; Putu Dina Susanti, Ni Luh; Ratih Comala Dewi, Ni Made; Aries Susanti, Ni Putu; Yudi Wahyu, I Made (Babali Publisher, 2024)
Background: Leadership is a crucial component of nursing management, where leadership style plays a significant role in its effective implementation. Challenges and barriers in leadership execution are essential aspects that need attention. Leadership is about the ability of an individual to influence the behavior of others towards a goal. This literature review aimed to identify effective leadership styles, as ideal leadership is a key aspiration for every organization. Methods: This study was a literature review using the PICO framework to formulate article questions. The search for articles was conducted via PubMed, Google Scholar, ScienceDirect, and Wiley using the keywords